2017
DOI: 10.1007/s00247-017-3955-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of radiation therapy on white matter of the corpus callosum: a diffusion tensor imaging study in children

Abstract: Background Despite improving survival rates, children are at risk for long-term cognitive and behavioral difficulties following the diagnosis and treatment of a brain tumor. Surgery, chemotherapy and radiation therapy have all been shown to impact the developing brain, especially the white matter. Objective The purpose of this study was to determine the long-term effects of radiation therapy on white matter integrity, as measured by diffusion tensor imaging, in pediatric brain tumor patients two years after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Importantly, lifesaving treatments also pose neurotoxic effects. For example, radiation dose and repeated surgeries have been associated with poorer outcomes in physical abilities, personal care, participation in routine activities, and overall quality of life 19‐22 …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, lifesaving treatments also pose neurotoxic effects. For example, radiation dose and repeated surgeries have been associated with poorer outcomes in physical abilities, personal care, participation in routine activities, and overall quality of life 19‐22 …”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) uses water molecules as a ubiquitous marker to provide an unprecedented and quantitative capability to probe tissue microstructures noninvasively [ 28 ]. It has been extensively used to evaluate microstructural changes in the white matter of the brain in vivo [ 29 , 30 ]. Previous studies using animal models have shown that synaptic plasticity and axonal growth are associated with increases in FA in recovered brain regions after stroke [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may particularly be the case given the role of white matter in cortical information processing and integration [29]. Links with damage to various white matter tracts have been reported [30,31]. It has also been demonstrated recently that in addition to long-term effects of radiotherapy on cognition, functional impairments in cognition and diffuse white matter changes may be detected as soon as 3 months after treatment with wider-field, cranial-spinal radiotherapy compared to local radiotherapy [32].…”
Section: Gam: Performance Iq (Piq)mentioning
confidence: 99%